Augustus Moore Herring papers - Herring, Augustus Moore, 1867-1926.
Patents for flying machines, papers and drawings for patent applications, and related legal papers. Includes the 1910 legal opinion from Wright Company v. Herring-Curtiss Company and a 1924 article concerning Herring.
Inventor in aeronautics and business associate of Glenn Curtiss in Herring-Curtiss Company.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Herring-Curtiss Company; Wright Company; Aeronautics -- United States; Flying-machines.; Flying-machines -- Patents; Businessmen; Inventors